PENGARUH PELATIHAN BAHASA INGGRIS TERHADAP KINERJA KARYAWAN DAILY WORKER DI HOTEL FAIRMONT JAKARTA - TITANIA AYU SETIA ASIH; RITA ARYANI; NADIA RISTA (GANEC SWARA, 2024)
This study analyzes the impact of English language training on the performance of daily worker employees at Fairmont Hotel Jakarta. Using quantitative methods and simple linear regression analysis, the study involved 67 randomly selected respondents. The results show a significant positive influence of English language training on employee performance, with 41.2% of performance variation explicable by language training. These findings affirm the importance of investing in language skill development as a strategy to enhance service quality in the hospitality industry. Theoretical and practical implications are discussed, including recommendations for developing more effective training programs and integrating language skills into human resource management in the hospitality sector. This research contributes significantly to understanding the critical role of English language skills in improving employee performance in the Indonesian hospitality industry.